Lincoln & liberty : wisdom for the ages - Morel, Lucas E., 1964- (University Press of Kentucky, 2014)
Since Abraham Lincoln's death, generations of Americans have studied his life, presidency, and leadership, often remaking him into a figure suited to the needs and interests of their own time. This illuminating volume takes a different approach to his political thought and practice. Here, a distinguished group of contributors argue that Lincoln's relevance today is best expressed by rendering an accurate portrait of him in his own era. They seek to understand Lincoln as he understood himself and as he attempted to make his ideas clear to his contemporaries. What emerges is a portrait of a prud.